Penyuluhan Terkait Penggunaan Tepung Komposit untuk Peningkatan Nutrisi Produk Pangan pada Ibu Hamil - Fitriana Mustikaningrum; Sudrajah Warajati Kisnawaty; Lisa Aprilia (Universitas Muhammadiyah Surakarta, 2025)
Based on reports from Ngemplak 1 Public Health Center (Puskesmas Ngemplak 1) in Sleman in 2023, the number of stunted children under five has not shown a significant decrease, although the prevalence has fallen below 14%. The prevalence of stunting was 12% in 2022 and decreased by only 0.2% in 2023. This figure is still below the Sleman District target, which requires a reduction to 7%. One of the groups at risk for stunting is pregnant women. The knowledge of pregnant women regarding food processing to improve the nutritional value of food products is crucial, as it is expected to positively influence their behavior in providing nutritious meals. Composite flour is a mixture of wheat flour and other types of flour aimed at enhancing the nutritional and sensory qualities of food products. Many pregnant women are still unfamiliar with how to process wheat-based products by incorporating composite flour to increase nutritional value. Therefore, this educational activity was conducted to improve pregnant women’s knowledge related to food processing using composite flour to enhance the nutritional content of wheat-based foods such as cookies, bread, and flakes. The health education session was delivered using lectures supported by PowerPoint media, videos, and leaflets. The results of the community service activity showed an increase in post-test scores compared to pre-test scores, indicating an improvement in knowledge about composite flour for enhancing the nutritional quality of food products for pregnant women.